Transforming Digital Public Service Systems to Enhance MSME Competitiveness and National Economic Growth in Indonesia - Tantri Relatami; Nursatyo Nursatyo (Jurnal Kajian dan Penelitian Umum, 2026)
The digital transformation of public services in Indonesia has become a critical catalyst for accelerating technology adoption among businesses, enhancing MSME competitiveness, and supporting national economic growth through data integration, bureaucratic simplification, and the development of an inclusive digital ecosystem. This study examines how digital public service reforms particularly the implementation of SPBE, OSS‑RBA, e‑tax, online halal certification, and MSME digital platforms drive MSME digitalization and strengthen economic competitiveness at the regional and national levels. Employing a descriptive‑analytical approach, the research analyzes policy frameworks, MSME digitalization trends, and interregional disparities in digital adoption and competitiveness. The findings demonstrate that digital public services significantly streamline administrative processes, reduce transaction costs, improve MSME productivity, and reinforce competitiveness, especially in regions with advanced digital infrastructure. The study concludes that the digital transformation of public services functions as a strategic enabler for MSME empowerment and national economic competitiveness by fostering bureaucratic efficiency, expanding access to essential services, and strengthening an integrated and inclusive digital ecosystem.